Do Social Interactions with Peers Affect Student Identity? - Mohammad Archi Maulyda; Muhammad Erfan (Qalam : Jurnal Ilmu Kependidikan, 2020)
This research is based on the observations and experiences of researchers, that at SMP Pawyatan Daha there are some students who are still doing things based on following along with friends, not based on themselves. For example, when a friend has a problem with a gang then triggers a fight, then his other friends will join in a fight with the intention of defending a friend even though they don't know what the problem is. This study aims to determine the effect of peer relations on self-identity. This study uses a quantitative research approach with comparative or ex-post facto causal techniques. The study population was 185, and the sample consisted of 47 research subjects of class VI students of SDN 26 Ampenan. Collecting data using peer questionnaire instruments and self-identity then based on the results of the distribution of questionnaires it was found that peers had a significant influence on the self-identity of grade VII students of SMP Pawyatan Daha 1 Kediri. Based on the results of the study using the product moment correlation test, the results obtained the value of r count â‰¥ r table or 0.295 â‰¥ 0.288. This means that there is an effect of peer interaction on the identity of class VII students of SMP Pawyatan Daha 1 Kediri. This result is supported by a simple linear regression test obtained by R Square with a result of 0.087. This means that the magnitude of the influence of peer interaction on self-identity is very weak.